Model rural health research unit's NS1-based serosurveillance recommends for vector control in rural villages of Jaipur district, Rajasthan, India - Meena, Chetram; Chouhan, Supriya; Yadav, Suresh; Thakor, Mahendra; Mohanty, Suman Sundar (Indian Journal of Health Sciences and Biomedical Research KLEU, 2023)
BACKGROUND: Infectious diseases are important public health issues in India. Rajasthan state reported 20,749 numbers of dengue fever (DF) cases in 2021, which was 10.73% of the country's total dengue cases. AIMS AND OBJECTIVES: The aim of the study was to diagnose fever cases in the nearby villages of Model Rural Health Research Unit (MRHRU) through the use of its diagnostic facility and to mitigate the diseases using appropriate control methods. MATERIALS AND METHODS: This is a community health center (CHC)-based serosurveillance study. The study subjects were the patients who reported at the Outpatient Department of the CHCs Bhanpur Kalan and Jamwa Ramgarh of Jaipur district in Rajasthan with clinical suspicion of DF. The study was conducted for 6 months from July to December. The serum samples received from CHC Bhanpur Kalan and Jamwa Ramgarh were tested for the detection of dengue antibodies against NS1 antigen at MRHRU. RESULTS: A total of 148 blood samples were received from CHC and were diagnosed with dengue NS1 at MRHRU. Out of 148 serum samples, 79 were male and 69 were female. Among the 148 samples subjected to the NS1 dengue enzyme-linked immunosorbent assay test, 33.1% were found to be positive for dengue, 63.5% were negative, and 3.37% were equivocal. Out of the 113 samples of Jamwa Ramgarh, 31.8% were found to be NS1 positive and 2.65% were equivocal, wherein 35 serum samples of Amber block were tested for diagnosis of NS1 test, and out of them, 37.14% were NS1 positive and 5.71% were equivocal. CONCLUSION: The number of dengue cases was observed to be higher, and control measure was taken to stop the spreading of the disease. Early and proper diagnosis of dengue cases is helpful in the treatment and control of disease. MRHRU facility was found to be effective in the containment of the disease.